A rare and life-threatening cause of pseudo-obstruction in two surgical patients. (23rd November 2010) - de Lloyd, AC; Munigoti, S; Davies, JS; Scott-Coombes, D
Abstract : We describe two patients who presented with non-mechanical bowel obstruction as a consequence of an underlying, undiagnosed phaeochromocytoma. The first patient was referred by his general practitioner with signs and symptoms of small bowel obstruction on a background of frequent constipation. An abdominal scan revealed an adrenal tumour (subsequently found to be a phaeochromocytoma) but no structural cause for obstruction. Treatment of the phaeochromocytoma was associated with prompt restoration of bowel function. The second patient was transferred to the intensive care unit on the 8th postoperative day following an elective hip joint replacement. Signs and symptoms of bowel obstruction together with labile blood pressure and progressive lactic acidosis prompted admission to the intensive treatment unit. An abdominal scan identified an infiltrative adrenal tumour but no mechanical cause for bowel obstruction. Histology confirmed a malignant phaeochromocytoma. Bowel obstruction as the presenting symptom of phaeochromocytoma is well described but rarely identified.